Decadal changes in fish assemblages in waters near the Ieodo ocean research station (East China Sea) in relation to climate change from 1984 to 2010 - Hwang, Kangseok; Jung, Sukgeun (Ocean science journal, 2012)
We compiled and analyzed past time-series data to evaluate changes in oceanographic conditions and marine ecosystems near the Ieodo ocean research station (IORS) in the East China Sea (N 31°15′–33°45′, E 124°15′–127°45′) in relation to longterm changes in climate and global warming. The environment data we used was a depth-specific time-series of temperature and salinity for the water columns at 175 fixed stations along 22 oceanographic lines in Korean waters, based on bimonthly measurements since 1961 taken by the National Fisheries Research & Development Institute. As an indicator for the ecosystem status of the waters off Ieodo, we analyzed species composition in biomass of fishes caught by Korean fishing vessels in the waters near the IORS (1984–2010) and summarized the data in relation to the environmental changes using canonical correspondence analysis (CCA). To detect step changes in the time-series of environmental factors, we applied a sequential t-test analysis of regime shift. Correspondence analysis detected a major shift in fish assemblage structure between 1990 and 1993: the dominant species was filefish during 1981–1992, but chub mackerel during 1992–2007. This shift in fish assemblage structure seemed to be related to the well-established 1989 regime shift in the North Pacific, which was confirmed again with respect to temperature in the Yellow Sea and the Korea Strait (but not in the waters off the IORS). In overall from 1984 to 2010, salinity was more important than water temperature in CCA, implying that the fluctuation of the Tsushima warm current is a most important force driving the long-term changes in fish assemblage structure in the waters off the IORS. Further multidisciplinary researches are required to identify oceanographic and biological processes that link climate-driven physical changes to fish recruitment and habitat range fluctuations.